CRESST - Angloher, G; Bauer, M; Bavykina, I; Bento, A; Brown, A; Bucci, C; Ciemniak, C; Coppi, C; Deuter, G; Feilitzsch, F; Hauff, D; Henry, S; et al. (2009)
The CRESST-II direct Dark Matter search is located in the Gran Sasso underground laboratories, Italy. CaWO4 crystals are used as scintillating targets for WIMP (weakly interacting massive particle) interactions. They are operated as cryogenic calorimeters in combination with a second cryogenic detector used to measure the scintillation light produced in the target crystal. For each particle interaction, the combination of phonon and light signals provides an event by event discrimination which allows to distinguish known particles (alphas, betas, gammas, neutrons) from the expected signal of WIMPs. A major upgrade of the setup comprises modifications of the shielding, installation of a muon-veto, and new read out electronics, as well as a new detector-support structure to accommodate up to 33 detector modules, i.e. 10 kg of target mass. The experiment was thereafter successfully commissioned in 2007. Data obtained during this commissioning phase from 2 detector modules are presented here. Combining the data collected with these two detector modules with data from one single module obtained during the CRESST-I phase, the experiment could already place a limit of ∼6 × 10-7 pb for the spin independent WIMP-nucleon scattering cross section at a WIMP mass of ∼60 GeV/c2. © BAS, BDP Sciences 2009.